Integrated Polypyrrole Flexible Conductors for Biochips and MEMS Applications. (9th August 2012) - Ofek Almog, Rakefet; Ben-Yoav, Hadar; Sverdlov, Yelena; Shmilovich, Tsvi; Krylov, Slava; Shacham-Diamand, Yosi
Abstract : Integrated polypyrrole, a conductive polymer, interconnects on polymeric substrates were microfabricated for flexible sensors and actuators applications. It allows manufacturing of moving polymeric microcomponents suitable, for example, for micro-optical-electromechanical (MOEMS) systems or implanted sensors. This generic technology allows producing "all polymer" components where the polymers serve as both the structural and the actuating materials. In this paper we present two possible novel architectures that integrate polypyrrole conductors with other structural polymers: (a) polypyrrole embedded into flexible polydimethylsiloxane (PDMS) matrix forming high aspect ratio electrodes and (b) polypyrrole deposited on planar structures. Self-aligned polypyrrole electropolymerization was developed and demonstrated for conducting polymer lines on either gold or copper seed layers. The electropolymerization process, using cyclic voltammetry from an electrolyte containing the monomer, is described, as well as the devices' characteristics. Finally, we discuss the effect of integrating conducting polymers with metal seed layer, thus enhancing the device durability and reliability.